Initial Experience with a Handheld Device Digital Imaging and Communications in Medicine Viewer: OsiriX Mobile on the iPhone. - Choudhri, Asim; Radvany, Martin (Journal of Digital Imaging, 2011)
Medical imaging is commonly used to diagnose many emergent conditions, as well as plan treatment. Digital images can be reviewed on almost any computing platform. Modern mobile phones and handheld devices are portable computing platforms with robust software programming interfaces, powerful processors, and high-resolution displays. OsiriX mobile, a new Digital Imaging and Communications in Medicine viewing program, is available for the iPhone/iPod touch platform. This raises the possibility of mobile review of diagnostic medical images to expedite diagnosis and treatment planning using a commercial off the shelf solution, facilitating communication among radiologists and referring clinicians.